Effect of different processing methods on the proximate composition, mineral content and functional properties of snail (Archachatina marginata) meat - Fabrice Tonfack Djikeng; Cecile Mazarine Mouto Ndambwe; Eric Serge Ngangoum; Bernard Tiencheu; Stephano Tambo Tene; Aduni Ufuan Achidi; Hilaire Macaire Womeni (Journal of Agriculture and Food Research, 2022)
This work aimed at assessing the effect of different processing methods on some nutrients and functional properties of snail meat. Meat samples were divided into seven groups. Six of them were processed and one served as control. The treatments applied were boiling, steaming, roasting, grilling, frying or their combinations. After that, they were characterized for their proximate composition, mineral content and the functional properties of their powders. Boiling for 12 min without water coupled to grilling or roasting; boiling with water or steaming for 24 min coupled to frying increased the protein content of snail meat from 41.65 to 58.62%. All treatments reduced its carbohydrate, sodium, potassium and phosphorus content, but increased its calcium (from 304 to 1892 mg/100 g) and magnesium (from 117.20 to 260.38 mg/100 g). Results of the functional properties are showed that the treatments applied increased the water absorption capacity (WAC), swelling capacity (SC), packed bulk density (PBD), emulsion stability (ES), hausner ratio and pH of snail meat powder. Boiling without water for 12 min coupled to roasting and boiling with water for 12 min coupled to frying decreased its oil absorption capacity (OAC). Frying decreased the loose bulk density (LBD) of the powder and increased its porosity. Snail meat can be a very good ingredient for the preparation and industrial formulation of food products.